The innovation of traditional dayak culinary products as a strategy to strengthen the creative economy in West Kotawaringin Regency - Armando Lampe, Normand; Evelina Buji, Grace; Sopather, Kembara (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
Innovation in traditional culinary products plays a crucial role in strengthening the creative economy in Kotawaringin Barat Regency. Traditional cuisine not only reflects local cultural identity but also has the potential to become a tourist attraction that enhances community welfare. The development of the creative economy through culinary innovation encompasses aspects such as presentation, packaging, and digital marketing strategies. However, innovation in this sector still faces various challenges, including limited access to technology, capital constraints, and the dilemma of preserving authenticity while adapting to market trends. Strategic efforts such as training, digital technology utilization, and collaboration with art communities serve as potential solutions. Research findings indicate that appropriate innovation can enhance the competitiveness of traditional cuisine and drive local economic growth. Therefore, a sustainable and collaborative approach is needed to ensure that traditional culinary innovation becomes a driving force for the creative economy in the region.